The Role of Dhikr in Counseling: Exploring Its Meaning and Relevance Through Qur’anic Interpretation - saputri, Endang; Zaini, Hasan; Irman, Irman (The Future of Education Journal, 2025)
This article is a literature review that examines the role of dhikr in the counseling process by tracing its meaning and relevance based on the interpretation of the Qur'an. This study uses a literature study method by collecting and analyzing various sources such as books, journals, and research results related to dhikr from an Islamic and psychological perspective. The results of the study show that dhikr in the Qur'an has a broad meaning, not only as verbal worship, but also as a way to get closer to Allah, form a positive attitude, and calm the soul. In Islamic counseling practice, dhikr functions as an effective spiritual therapy technique to help individuals overcome anxiety, stress, and other psychological problems. Various studies support that the application of dhikr in counseling sessions can increase inner peace, mental focus, and strengthen the spiritual aspect of psychological health. In addition, dhikr has also been proven relevant as a relaxation and therapy method that supports the overall mental healing process in accordance with the spiritual values ​​taught in the Qur'an. Therefore, dhikr has an important role in Islamic counseling both as a preventive and curative measure, as well as being a culturally sensitive approach to improving mental health in the Muslim community.